(untitled) - Jonathan Sperber (Cambridge, New York, 1993)
The book describes the events of the various national revolutions (both in 1848, and in the subsequent, often neglected period 1849 - 1851), analyzes the contrasting social and political tensions underlying the outbreak of revolution, explores the different varieties of revolutionary experience and compares the events of 1848 - 1851 with both the previous wave of 1789 -1795 and the successor of 1917 - 1923
Keywords: europe - history - 1848-9,revolutions - europe - history - 20th century